Electrophoretic pattern of hereditary haemoglobin disorders in a referral centre: a one year study - Karim, Md Mostafil; Yousuf, AKM Abu; Akhter, Shahina; Ahmad, Mushtaq; Sultana, Sharmeen; Al-Azad, Md Abdus Samad; Karim, Md Iqbal (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: The inherited disorders of haemoglobin are the commonest single-gene disorders with an estimated carrier rate of 7% among the world population. They occur at particularly high frequencies in population of the tropical and subtropical belt. Objective: To find out the electrophoretic pattern of haemoglobin disorders and to evaluate and compare the diseases in study population. Methods: A total number of 1370 subjects of both sexes with age range from 6 months to 73 years were included in the study. The study was conducted in Haematology Department of Armed Forces Institute of Pathology, Dhaka. It was carried out from January to December 2012. Patients were selected on the basis of morphological blood film examination and electrophoresis on cellulose acetate at PH 8.6. Results: Among the 1370 subjects, Beta thalassaemia trait was observed in 532(38.83%) cases, HbE trait in 313(22.85%), HbE-Beta thalassaemia in 282(20.58%), HbE disease in 146(10.66%) and Beta thalassaemia major in 97(7.08%) cases. Conclusion: The study reveals that, hereditary haemoglobin disorders are common in Bangladesh and are inherited as autosomal recessive Mendelian pattern affecting both male and female. DOI: http://dx.doi.org/10.3329/jafmc.v9i2.21827 Journal of Armed Forces Medical College Bangladesh Vol.9(2) 2013